2013
DOI: 10.14309/00000434-201310001-00112
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Adenomas in Familial Adenomatous Polyposis Are Common, But Subtle, and Have a Benign Course

Abstract: Background: Patients with familial adenomatous polyposis (FAP) are known to have an increased risk for gastric adenomas. The clinical features of gastric adenomas in FAP have not been well characterized, and there is a lack of standardized approaches to the management of these lesions. Aims: To study the endoscopic appearance, risk factors, clinical course, and response to therapy of gastric adenomas in patients with FAP. Methods: We retrospectively reviewed the records of 97 patients with FAP who underwent es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…Indeed, a greater proportion of gastric adenoma cases than would normally be expected had a personal or family history of desmoid. Interestingly, Ngamruengphong et al also reported that patients with FAP and a gastric adenoma were significantly more likely to have had a desmoid tumour compared to patients without a history of a gastric adenoma, 5/9 (56%) and 19/88 (22%), respectively [13]. This was comparable to our study's findings.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Indeed, a greater proportion of gastric adenoma cases than would normally be expected had a personal or family history of desmoid. Interestingly, Ngamruengphong et al also reported that patients with FAP and a gastric adenoma were significantly more likely to have had a desmoid tumour compared to patients without a history of a gastric adenoma, 5/9 (56%) and 19/88 (22%), respectively [13]. This was comparable to our study's findings.…”
Section: Discussionsupporting
confidence: 88%
“…Spigelman et al previously reported that patients with gastric adenomas had a higher incidence of severe duodenal polyposis [18]. A more recent study by Ngamruengphong et al failed to show an association between gastric adenomas and duodenal disease in FAP [13].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations